Paleoenvironmental inference and anatomy of new remains of Notosuchus terrestris Woodward, 1896 (Crocodyliformes: Mesoeucrocodylia) from Bajo de la Carpa Formation, Neuquén City, Argentina - Roussillon, Emmanuel Facundo (2021)
A new material of Mesoeucrocodylia is recognized at Bajo de la Carpa Formation, Neuquén Group (Upper Cretaceous, Coniacian-Santonian?). The fossil site is located between Dr. Ramón Avenue and 9 de Julio Diagonal, Neuquén City (38° 56’ 34” S and 68° 03’ 58” O), Neuquén province